Village schools - Proctor, John (Oxford ; Oxford University Press, Karachi, 2005)
"Village Schools: A History of Rural Elementary Education from the 18th to the 21st Century in Prose and Verse" by John Proctor, published in 2005 by Oxford University Press, offers a comprehensive exploration of rural education's evolution over three centuries. The book utilizes memoirs, contemporary observations, and verse to provide readers with insights into the experiences of pupils, teachers, inspectors, and visitors in various village schools. It covers a range of educational institutions, including dame schools, hedge schools, common day schools, Muslim maktabs, and Hindu pathasalas, highlighting the diverse nature of rural education both in the United Kingdom and internationally.